BERSIH DIRI BERSIH LINGKUNGAN BERSIH NEGARA - Faris, Muhammad; Indah Muslimah, Alfiana; Putra, Purnama (An-Nizam, 2023)
Community servicel discusses the importance of awareness regarding personal hygiene, clean environment, and a clean nation through socialization among junior high school students is highlighted in this journal. The issues addressed include the students’ limited understanding of the importance of maintaining personal hygiene and a clean environment, as well as the positive impacts on both the village and the nation. The research implementation method involves an educational approach through seminars, creativity, and interactive discussions, facilitated in collaboration and synergy with relevant stakeholders and supporters. The outcomes of the activities will demonstrate an enhanced understanding among students concerning personal hygiene, the environment, and their social responsibilities as citizens. This socialization is also anticipated to successfully increase students participation in environmental cleanliness activities, inspiring positive actions on a small scale that contribute to the improvement of their surrounding environment. In conclusion, an educational approach and effective socialization in instilling the values of personal hygiene, environmental consciousness, and nationalism in junior high school students can shape a responsible and conscientious younger generation, committed to cleanliness and the progress of both the village and the nation.